Videofluoroscopy of the aerodigestive tract in Phoca vitulina: reshaping perspectives on translational medicine - Skoretz, Stacey A.; Adams, Arlo; Vogl, A. Wayne; Raverty, Stephen; Haulena, Martin; Stahl, Hillary; Dawson, Camilla (Frontiers in Veterinary Science, 2024)
Thousands of rescued harbour seals (Phoca vitulina) require rehabilitation worldwide. Many require resource intensive gavage feeding due to abandonment soon after birth. Little is known about seal swallowing, therefore, our primary objective was to determine the feasibility of conducting videofluoroscopic swallowing studies (VFS) on seal pups prior to their release. Secondarily, we propose swallowing phase descriptions.We adapted a VFS approach used in humans and our feasibility parameters included: bolus detection and consumption, and number of analyzable swallowing events. Unrestrained seals were imaged in a dry environment using a Siemens mobile c-arm fluoroscopy unit. Oral boluses were thawed herring injected with liquid barium suspension (105% w/v). Two independent raters described swallows using a standardized approach with results summarized descriptively.We successfully completed freely-behaving VFS with two infant seals (1 male: 8 wks, 3 d; 1 female: 5 wks, 3 d). Both consumed five boluses with six fully analyzable swallowing events. We describe four swallow phases: preparatory, prehension, oropharyngeal and esophageal. Airway protection likely occurs in two ways: 1) during the preparatory phase through modified corniculate cartilage contact with the glottis and 2) with soft palate contact to the base of tongue prior to swallow initiation.We have conducted a unique VFS approach on rehabilitated seals, prior to their release. We have described airway protection and suggest that swallowing is initiated earlier in the feeding process than described previously. This protocol success will afford: 1) collection of normative swallowing data, and 2) future knowledge translation from humans to seals.